Peste des petits ruminants in Pakistan; past, present and future perspectives - Abubakar, Muhammad (J Anim Sci Technol, 2015)
Peste des petits ruminants (PPR) is considered to be one of the main constraints to enhancing the productivity of goats and sheep in regions where it is present and becoming endemic. PPR was recognized in Pakistan in early 1990s but got importance during the Participatory Disease Surveillance (PDS) of Rinderpest Eradication Campaign. Lot of research work has been initiated during last decade towards disease epidemiology, risk factor recognition, laboratory diagnosis, vaccination and demonstration of control strategies. Although there are ongoing projects working towards the progressive control of the disease in country yet there is need to have a national level control program for PPR. Also there is need to have comprehensive social economic surveys, disease hot spot recognition and identification of role of other species in disease transmission. With combined efforts of local and national authorities and political will, there is high likelihood that this devastating disease can be controlled and eventually eradicated in near future.